Development of active biodegradable films based on chitosan and essential oil to prevent infestation of Plodia interpunctella (Lepidoptera: Pyralidae). (December 2022) - Jesser, E.; Castillo, L.; Alonso, Y.; Urrutia, R.I.; Murray, A.P.; Domini, C.; Werdin-González, J.O.
Abstract: Plodia interpunctella Hübner (Lepidoptera: Pyralidae) is probably the most common moth pest of stored products. Its larvae are considered very effective packaging penetrators, causing serious losses. Therefore, the development of new food packaging technologies to prevent larvae infestation is crucial. In the present work, geranium and peppermint essential oils (EO) were used to elaborate chitosan (Qx) based films (Qx-EO films) at different concentrations (0% (control), 0.1%, 0.25% and 0.5% w/w). The Qx-EO films were tested in repellent and penetration assays for 72 h and 15 days, respectively. In both bioassays, most effective Qx-EO films were those containing geranium and peppermint EO at 0.5% w/w. In repellent assays, Qx-geranium EO films were more effective than Qx-peppermint EO films. In penetration assays, both films reduced penetration percentage to 10% (penetration percentage for control ≈ 50%). Then, possible structural changes, thermal stability and mechanical properties of Qx films containing EOs at 0.5% w/w were analyzed. The loading efficiency of Qx-geranium EO and peppermint EO films were close to 90% and 35%, respectively. It was demonstrated that EO incorporation allows conserving mechanical properties of control films. It is important to emphasize that these films showed repellent activity and could prevent contamination with P. interpunctella larvae . Graphical Abstract: ga1 Highlights: Geranium and peppermint Qx-EO films were elaborated at different concentrations. Qx-EO films at 0.5% were repellent against P. interpunctella larvae for 72 h. Qx-EO films at 0.5% prevent contamination with Plodia interpunctella larvae for 15 days. EO incorporation allows conserving mechanical properties of Qx films.